2021
DOI: 10.3390/app11020810
|View full text |Cite
|
Sign up to set email alerts
|

Coal Fly Ash–Clay Based Geopolymer-Incorporating Electric Arc Furnace Dust (EAFD): Leaching Behavior and Geochemical Modeling

Abstract: The recent recovery processes of electric arc furnace dust (EAFD) include stabilization within materials with potential uses in the construction sector. The stabilization of EAFD by alkaline activation of different alumina-silicates, resulting in low-cost and environmentally friendly materials. The leaching standards within the different European regulations allow evaluating waste materials and products. This work aims to study the introduction of EAFD in FA–clay geopolymers, assessing the environmental and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…As can be seen from the above numbers, BF-BOF dust represents a significantly higher contribution (2-4 times) to the quantity of steel dust compared to EAF dust. Due to the chemical nature of these dusts, they are regarded as hazardous and must be chemically / thermally treated prior to disposing in landfills, which is expensive [41]. Alternative methods for (economically) processing these BOF dusts are therefore important areas of research.…”
Section: Quantifying Production Of Waste From Galvanised Steel Produc...mentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen from the above numbers, BF-BOF dust represents a significantly higher contribution (2-4 times) to the quantity of steel dust compared to EAF dust. Due to the chemical nature of these dusts, they are regarded as hazardous and must be chemically / thermally treated prior to disposing in landfills, which is expensive [41]. Alternative methods for (economically) processing these BOF dusts are therefore important areas of research.…”
Section: Quantifying Production Of Waste From Galvanised Steel Produc...mentioning
confidence: 99%
“…In addition, there needs to be increased focus on producing "quality" waste which would be better suited for further processing [42]. Currently the economic threshold for the recycling of EAF dust is determined by the zinc content being higher than 15% [41,42]. EAF dusts containing less than this threshold of zinc are currently sent to landfill, which in the EU reportedly makes up two thirds of their EAF dust production [41].…”
Section: Quantifying Production Of Waste From Galvanised Steel Produc...mentioning
confidence: 99%
“…El-eswed [ 108 ] proposed that Cu can replace Si in the geopolymer structure, being similar to Pb. Moreover, the leaching of Cu was always evaluated in terms of geopolymers synthesized from fly ash and industrial sludge [ 142 ], mine tailing [ 143 ], lead–zinc smelting slag [ 75 ], sludge incineration residue [ 144 ], red mud, and municipal solid waste incineration fly ash (MSWI) [ 145 , 146 , 147 ], melting slag of MSWI and bottom ash [ 148 ], electrolytic manganese residue [ 149 ], electric arc furnace dust [ 150 ], etc. Importantly, the leaching concentration of Cu can be satisfied with related standards.…”
Section: Geopolymer-based S/s Processmentioning
confidence: 99%
“…From a quantity perspective, it has been reported that for every ton of steel manufacturing, approximately 15-20 kg are generated as a by-product [2,3] . According to recently published research, only about 2.5 of the 6 Mmt of EAFD produced annually worldwide are recycled [4] .…”
Section: Introductionmentioning
confidence: 99%